2007
DOI: 10.1007/s00020-007-1489-x
|View full text |Cite
|
Sign up to set email alerts
|

Collinear Systems and Normal Contractive Projections on JBW*-Triples

Abstract: Given a family {x k } k∈K of elements x k in the predual A * of a JBW * -triple A, such that the support tripotents e k of x k form a collinear system in the sense of [31], necessary and sufficient criteria for the existence of a contractive projection from A * onto the subspace lin{x k : k ∈ K} n are provided. Preparatory to these results, and interesting in itself, is a set of necessary and sufficient algebraic conditions upon a contractive projection P on A for its range P A to be a subtriple. The results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The partial isometries of B(H, K) are precisely the tripotent elements. In [16] Loos showed that when C is a finite-dimensional Cartan factor, then the group Inn(C) acts transitively on the set U r (C) of tripotents of rank r in C. An analogous statement for Hilbert spaces of arbitrary dimension was proved in [11]. The goal of the present article is to generalize that result to all Cartan-factors.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The partial isometries of B(H, K) are precisely the tripotent elements. In [16] Loos showed that when C is a finite-dimensional Cartan factor, then the group Inn(C) acts transitively on the set U r (C) of tripotents of rank r in C. An analogous statement for Hilbert spaces of arbitrary dimension was proved in [11]. The goal of the present article is to generalize that result to all Cartan-factors.…”
Section: Introductionmentioning
confidence: 68%
“…The above-cited works show that the geodesics in those manifolds are given by paths of inner automorphisms of the corresponding JBW * -triple. The arguments presented in [11] and [12] show that the transitivity of Inn(C) on U 1 (C) is closely connected to the problem of the existence of contractive projections onto subtriples of JB * -triples or JBW * -triples.…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider atomic subtriples with finite-dimensional Cartan-factors of any of the six types in a general JBW * -triple A. We extend those main results of [21] concerning the relationships of contractive projections on A and on the pre-dual A * with the group Inn(A) of inner automorphisms and its Banach-Lie algebra inn(A) of inner derivations of A.…”
Section: Introductionmentioning
confidence: 85%
“…This underpins the principle of commutation as a simple algebraic characterization of the geometric property of contractivity. The said principle was first observed in the context of Hilbert spaces equipped with the Jordan-triple product of type-I Cartan-factors [21]. Here we consider atomic subtriples with finite-dimensional Cartan-factors of any of the six types in a general JBW * -triple A.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the main results presented in this article were obtained in the authors Ph.D. thesis [15]. He wishes to acknowledge the advise of the late G. T. Rüttimann, University of Berne, and of C. M. Edwards, University of Oxford, as well as the support received by H. Carnal, University of Berne.…”
mentioning
confidence: 99%